2020
DOI: 10.1007/s10734-020-00606-2
|View full text |Cite
|
Sign up to set email alerts
|

Reaching for different ends through tenure track—institutional logics in university career systems

Abstract: In this study, we used the institutional logics perspective to identify the logics underpinning the tenure track career system, how the logics manifest themselves in recruitment and performance management and how academic leaders and academics negotiate between the logics. The study contributes to research on governance dynamics in academia and to universities’ organisational transformation in the context of strategic actorhood. The data comprised interviews with academic leaders (vice-rectors, deans, departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…This study does not question the cases of inbreeding that have surfaced or that there is a lack of mobility. However, this study has shown that academic recruitment is a tangle of different practices and ideals that sometimes pull in different directions, and recruitment practices include a constant negotiation between different logics (as also shown by Pietilä & Pinheiro, 2020). Heads of departments who are placed in the middle note that their recruitment practices are the result of several considerations, balancing different ideals.…”
Section: Choice Of Candidatementioning
confidence: 83%
See 1 more Smart Citation
“…This study does not question the cases of inbreeding that have surfaced or that there is a lack of mobility. However, this study has shown that academic recruitment is a tangle of different practices and ideals that sometimes pull in different directions, and recruitment practices include a constant negotiation between different logics (as also shown by Pietilä & Pinheiro, 2020). Heads of departments who are placed in the middle note that their recruitment practices are the result of several considerations, balancing different ideals.…”
Section: Choice Of Candidatementioning
confidence: 83%
“…Academic recruitment practices make up an interesting case because of the high level of importance and strategic potential ascribed to them and because they offer us an interesting mix of logics and ways of thinking (Pietilä & Pinheiro, 2020). The seven logics of family, community, religion, state, market, profession and corporation formulated by Thornton et al (2012) were used as a starting point to explore the tensions in recruitment practices at universities in Sweden.…”
Section: Institutional Logicsmentioning
confidence: 99%
“…Future research could also investigate the position of Aalto Mikkeli within the academic labor markets in Finland (e.g. Pietilä , 2019;Pietilä & Pinheiro, 2021) and the other Nordic countries .…”
Section: Discussionmentioning
confidence: 99%
“…& The responses of individuals, particularly early career staff, to less certain conditions and the increasing pressures of academic life (Archer, 2008;Gornall et al, 2014;Jones et al, 2020;Marini, 2019;McAlpine, 2010;McAlpine & Amundsen, 2018;Ortlieb & Weiss, 2018;Rosewell & Ashwin, 2019;Ylijoki and Henriksson, 2017;Ylijoki & Ursin, 2013;Yudkevich et al, 2015). & The impact of career structures at national levels, including the use of tenure track arrangements and market mechanisms such as the UK Research Excellence Framework and the knowledge economy (Coates & Goedegebuure, 2010;Enders & de Weert, 2009;Musselin, 2013;Pietilä, 2017;Pietilä & Pinheiro, 2020;Strike & Taylor, 2009;Watermeyer & Tomlinson, 2021). & Career typologies focusing on the individual, including the concept of the kaleidoscope career (Mainiero & Sullivan, 2006), suggesting that the individual has multiple considerations when making decisions about their career (Baruch, 2013;Sullivan & Baruch, 2009), which can involve "intersecting identities" (professional, personal and relational) (Pifer & Baker, 2016: 192).…”
Section: Literaturementioning
confidence: 99%